Paraoxonase 2 attenuates macrophage triglyceride accumulation via inhibition of diacylglycerol acyltransferase 1 - Mira Rosenblat; Raymond Coleman; Srinivasa T. Reddy; Michael Aviram (Journal of Lipid Research, 2009)
This study questioned the role of paraoxonase 2 (PON2) in attenuation of macrophage lipids accumulation. Mouse peritoneal macrophages (MPMs) harvested from PON2-deficient mice versus control C57BL/6 mice, look like foam cells and were larger in size and filled with lipid droplets. Macrophage triglyceride (but not cholesterol) content, biosynthesis rate, and microsomal acyl-CoA:diacylglycerol acyltransferase 1 (DGAT1) activity (not mRNA and protein) in PON2-deficient versus control MPM were all significantly increased by 4.6-, 3.6-, and 4.4-fold, respectively. Similarly, microsomal DGAT1 activity and cellular triglyceride content were significantly decreased in human PON2-transfected cells as well as upon incubation of PON2-deficient MPM with recombinant PON2. In all the above experimental systems, PON2 also decreased macrophage oxidative state. Incubation of PON2-deficient MPM with the free radicals generator 2,2′-amidinopropane hydrochloride increased cellular oxidative stress and DGAT1 activity by 2.2- and 3.4-fold, respectively, whereas incubation of microsomes from PON2-deficient MPM with superoxide dismutase decreased DGAT1 activity by 40%. We thus conclude that PON2 attenuates macrophage triglyceride accumulation and foam cell formation via inhibition of microsomal DGAT1 activity, which appears to be sensitive to oxidative state.